Genome-wide identification and expression analysis of proline synthesis and catabolism genes in kiwifruit: exploring the role of AcP5CS1 in salt tolerance - Yang, Jun; Qian, Cheng; Chen, Can; Liu, Guoqi; Zhen, Xiaowei; Hussain, Quaid; Lyu, Shiheng; Ling, Chengcheng (Frontiers in Plant Science, 2025)
The regulation of proline metabolism is critical for enhancing plant stress tolerance by promoting proline accumulation under abiotic stress conditions. Key enzymes in this pathway include Δ1-pyrroline-5-carboxylate synthase (P5CS), pyrroline-5-carboxylate reductase (P5CR), ornithine δ-aminotransferase (δ-OAT), proline dehydrogenase (PDH), and pyrroline-5-carboxylate dehydrogenase (P5CDH). Despite their importance, comprehensive identification and characterization of these gene families in kiwifruit (Actinidia chinensis) remain unexplored. This study identified two AcP5CSs, one AcP5CR, one AcOAT, three AcPDHs, and one AcP5CDH within the kiwifruit genome. This research comprehensively examined phylogenetic tree, gene structure, motif analysis, cis-regulatory elements and chromosomal distributions analysis, as well as expression profiles under abiotic stresses and hormonal stress. Under salt stress, transcriptional profiling showed marked upregulation of AcP5CS1, AcP5CR, and AcOAT, while AcP5CDH was significantly suppressed, as confirmed by qRT-PCR. Functional analysis demonstrated that AcP5CS1 overexpression in Arabidopsis significantly enhanced salt tolerance. The correlation results indicated a strong association between the AcNAC30 transcription factors (TFs) and the expression of AcP5CS1. Mechanistic studies using dual-luciferase and electrophoretic mobility shift assays (EMSA) confirmed that AcNAC30 directly binds to the AcP5CS1 promoter. Therefore, we speculated that AcNAC30 likely enhances proline accumulation under salt stress by upregulating the expression of proline metabolic pathway genes. These findings elucidate the genomic architecture of proline metabolic genes in kiwifruit and establish their pivotal role in mediating abiotic stress tolerance.